2021
DOI: 10.47068/ctns.2021.v10i19.034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of High Temperature Treatments on Tomato Leaves at Two Developmental Phases

Abstract: This study was conducted to investigate the effects of high temperatures on three tomato cultivars at first bloom and yield stages. The leaves were subjected to high temperature stress at 35, 40, 45, 50, 55 and 60°C with gradual increments every 30-minutes in both stages. Samples were analyzed for total chlorophyll (Chl), carotenoid (Car), ascorbic acid (AsA), glutathione (GSH), total soluble protein (TSP) contents. Besides, protein profiles were determined with SDS-PAGE. Heat stress decreased Chl content in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Tokyol and Turhan (2019) found that the TSP content of green bean genotypes reduced and/or induced with heat stress. Besides, in tomato (Turhan et al, 2021) and cucumber (Ergin et al, 2021) plants fluctuations in the TSP content under high temperatures were reported. Besides, the TSP contents of zucchini plants were not affected by the temperature, while the TSP content of melon plants did not change up to 50°C and then decreased with the increase in temperature (Ergin et al, 2021).…”
Section: Figure 3 Effects Of Heat Stress On Acidic (Panel A) and Basi...mentioning
confidence: 98%
See 2 more Smart Citations
“…Tokyol and Turhan (2019) found that the TSP content of green bean genotypes reduced and/or induced with heat stress. Besides, in tomato (Turhan et al, 2021) and cucumber (Ergin et al, 2021) plants fluctuations in the TSP content under high temperatures were reported. Besides, the TSP contents of zucchini plants were not affected by the temperature, while the TSP content of melon plants did not change up to 50°C and then decreased with the increase in temperature (Ergin et al, 2021).…”
Section: Figure 3 Effects Of Heat Stress On Acidic (Panel A) and Basi...mentioning
confidence: 98%
“…Likewise, in tomato plants protein bands ranging between 17-89 kDa (at first bloom stage) and 13-89 kDa (at yield stage) were detected, of which a protein band of 43 kDa was found to be only in cv. 'Yaren' (relatively tolerant) at yield stage (Turhan et al, 2021). Besides, Ergin et al (2016) indicated that heat stress resulted in new protein bands and decreases/disappearance of some proteins in strawberry plants.…”
Section: Figure 3 Effects Of Heat Stress On Acidic (Panel A) and Basi...mentioning
confidence: 99%
See 1 more Smart Citation